Konseling Individual Terhadap Anak Yang Memiliki Keterlambatan Dalam Belajar (Studi Kasus Pada Siswa Kelas II Dan III Di SD Negeri 08 Pasar 60 Nagari Batang Arah Tapan) - Annisa Aulia Pratama; Ahmad Khairul Nuzuli; Winda Oktaviana (CV. Multi Kreasi Media, 2023)
School as an educational institution and is a means in order to achieve these educational goals. The purpose of this study was to determine Individual Counseling for Children Who Have Learning Delays in Nagari Batang Arah Tapan. The approach in this research is a descriptive qualitative approach. Data collection techniques used are observation, diagnostic tests and documentation. The problems obtained during the observation were class II and III students at SDN 08 Pasar 60 Nagari Batang Arah Tapan, namely delays in learning in the form of students who could not read and had difficulty recognizing letters of the alphabet. Therefore individual guidance and counseling services require observation, documentation and diagnostic tests in increasing students' learning knowledge at SDN 08 Pasar 60 Nagari Batang Arah Tapan, guidance and counseling teachers are able to become supervisors, mentors, and controllers.